2000
DOI: 10.1021/jm990321p
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Highly Potent and Selective A1 Adenosine Antagonists:  Structure−Affinity Profile of a Series of 1,8-Naphthyridine Derivatives

Abstract: A series of 1,8-naphthyridine derivatives (12-36), bearing a phenyl group in position 2 and various substituents in positions 4 and 7, were synthesized in an attempt to obtain potent, selective antagonists for the A1 adenosine receptor subtype. The compounds were tested to evaluate their affinity for A1 compared with A2A and A3 adenosine receptor subtypes. In binding studies in bovine brain cortical membranes, most of the compounds showed an affinity for A1 receptors in the low nanomolar range and two in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…After observing that 4.1G can influence A 1 AR ligand-binding properties, we next examined if 4.1G expression affects A 1 AR function. Because A 1 AR activation inhibits adenylate cyclase activity [22], we tested if 4.1G affected A 1 AR-mediated inhibition of cAMP accumulation in A 1 R-CHO cells.…”
Section: 1g Inhibits a 1 Ar-mediated Inhibition Of Camp Accumulationmentioning
confidence: 99%
“…After observing that 4.1G can influence A 1 AR ligand-binding properties, we next examined if 4.1G expression affects A 1 AR function. Because A 1 AR activation inhibits adenylate cyclase activity [22], we tested if 4.1G affected A 1 AR-mediated inhibition of cAMP accumulation in A 1 R-CHO cells.…”
Section: 1g Inhibits a 1 Ar-mediated Inhibition Of Camp Accumulationmentioning
confidence: 99%
“…In addition, although the cloning of the human adenosine A 1 receptor was reported in 1992, many even very recently developed compounds have not been tested at this receptor. One particularly relevant and very recent example are the naphthyridines reported by Ferrarini et al [119] [120]. The quoted 94% amino-acid homology between the human and bovine A 1 receptors concealed the discrepancies in affinity that was experienced by these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Siddiqi et al screened many compounds and found some affinity for naphthyridine derivatives [61]. More recently, Ferrarini et al published more lucrative substitution about the 1,8-naphthyridine ring [119]. At C(7), a number of halides were used, showing an almost equal effect across the board.…”
Section: The Adenosine a 1 Receptormentioning
confidence: 99%
“…The assumed synthetic approach to obtain the target compounds was achieved by using the key intermediate 7-methyl-2-phenyl-1,8-naphthyridin-4(1H)-one (1) [27]. A series of 3-((substituted amino) methyl)-7-methyl -2-phenyl-1,8naphthyridin-4-one (2a-e) was obtained by the reaction of 7-methyl-2-phenyl-1,8-naphthyridinone (1) with paraformaldehyde and the appropriate secondary amine namely, piperidine, piperazine, morpholine, diethylamine and sulphanilimide in absolute ethanol, under either traditional heating or ultrasound irradiation through Mannich reaction to give the products 2a-e (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%